2005
DOI: 10.1037/1076-8998.10.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Effective Group Training Techniques in Job-Search Training.

Abstract: The aim was to examine the effects of group training techniques in job-search training on later reemployment and mental health. The participants were 278 unemployed workers in Finland in 71 job-search training groups. Five group-level dimensions of training were identified. The results of hierarchical linear modeling demonstrated that preparation for setbacks at the group level significantly predicted decreased psychological distress and decreased symptoms of depression at the half-year follow-up. Trainer skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 31 publications
(55 reference statements)
4
24
0
Order By: Relevance
“…The proximal effect of the intervention showed a significant increase in employment preparedness, which in the long -term follow -up resulted in higher employment rate and better quality employment compared to controls. Both of these studies demonstrated results that have been found in other studies with other participant populations (Vinokur et al, 1995;Vuori et al, 2005;Vuori et al, 2002;Vuori et al, 2012).…”
Section: Educational Characteristicssupporting
confidence: 74%
“…The proximal effect of the intervention showed a significant increase in employment preparedness, which in the long -term follow -up resulted in higher employment rate and better quality employment compared to controls. Both of these studies demonstrated results that have been found in other studies with other participant populations (Vinokur et al, 1995;Vuori et al, 2005;Vuori et al, 2002;Vuori et al, 2012).…”
Section: Educational Characteristicssupporting
confidence: 74%
“…Next, we used the meta-analyzed correlations in a meta-analytic path model to examine job search self-efficacy and job-search intensity as potential mediators of the relationship of age and reemployment status and speed (Viswesvaran & Ones, 1995).…”
Section: Meta-analytic Findingsmentioning
confidence: 99%
“…This preparedness is strengthened through concrete advice, social support and examples of new ways of action received during the intervention. Based on previous studies, it seems that the component of inoculation against setbacks is especially effective in reducing the risk of depression 29 30…”
Section: Discussionmentioning
confidence: 99%
“…One resource-enhancing group intervention25 was developed based on earlier experiences in preventive group methods aimed at empowering people and increasing their career preparedness during unemployment 26–29. Further development of the intervention was guided by analyses of successful interventions and the Michigan Prevention Research Centre principles for effective group training 19 30…”
Section: Introductionmentioning
confidence: 99%